Genetic Differentiation among Maruca vitrata F. (Lepidoptera: Crambidae) Populations on Cultivated Cowpea and Wild Host Plants: Implications for Insect Resistance Management and Biological Control Strategies - Agunbiade, T.A.; Coates, B.S.; Datinon, B.; Djouaka, R.F.; Sun, W.; Tamo, Manuele; Pittendrigh, Barry Robert (Public Library of Science, 2014)
Maruca vitrata Fabricius (Lepidoptera: Crambidae) is a polyphagous insect pest that feeds on a variety of leguminous plantsin the tropics and subtropics. The contribution of host-associated genetic variation on population structure wasinvestigated using analysis of mitochondrial cytochrome oxidase 1 (cox1) sequence and microsatellite marker data from M.vitrata collected from cultivated cowpea (Vigna unguiculata L. Walp.), and alternative host plants Pueraria phaseoloides(Roxb.) Benth. var. javanica (Benth.) Baker, Loncocarpus sericeus (Poir), and Tephrosia candida (Roxb.). Analyses ofmicrosatellite data revealed a significant global FST estimate of 0.05 (P#0.001). The program STRUCTURE estimated 2genotypic clusters (co-ancestries) on the four host plants across 3 geographic locations, but little geographic variation waspredicted among genotypes from different geographic locations using analysis of molecular variance (AMOVA; amonggroup variation 20.68%) or F-statistics (FSTLoc =20.01; P = 0.62). These results were corroborated by mitochondrialhaplotype data (QSTLoc = 0.05; P = 0.92). In contrast, genotypes obtained from different host plants showed low butsignificant levels of genetic variation (FSTHost = 0.04; P = 0.01), which accounted for 4.08% of the total genetic variation, butwas not congruent with mitochondrial haplotype analyses (QSTHost = 0.06; P = 0.27). Variation among host plants at a locationand host plants among locations showed no consistent evidence for M. vitrata population subdivision. These resultssuggest that host plants do not significantly influence the genetic structure of M. vitrata, and this has implications forbiocontrol agent releases as well as insecticide resistance management (IRM) for M. vitrata in West Africa.Ci